Towards understanding EFL Research: Developing a well-designed teaching material - Zulfikar, Teuku; Emawati, Emawati; Mujiburrahman; Alfa Karim, Cut Fadhilah (English Language Teaching Educational Journal, 2025)
This study investigates how English as Foreign Language (EFL) research can be better understood by developing well-designed teaching materials that support students’ research literacy. Grounded in the need to enhance novice EFL researchers’ capacity to conceptualize, plan, and conduct research, this study explores the essential components of effective instructional materials and how these materials can scaffold students’ engagement with EFL research processes. Data were generated through focus group discussions (FGDs) conducted across three universities, involving a total of 15 participants comprising lecturers teaching research methodology in ELT. The FGDs examined participants’ experiences, challenges, and expectations regarding current research-related teaching materials. Thematic analysis revealed that students often struggle with identifying research problems, understanding methodological choices, and connecting theories to research practices, largely due to fragmented or overly theoretical materials. Participants emphasized the importance of structured, practice-oriented, and contextually relevant teaching materials that guide learners step-by-step through research tasks. Based on these insights, this study proposes a framework for designing pedagogically robust EFL research materials that integrate clear explanations, worked examples, reflective tasks, and opportunities for guided practice. The findings contribute to improving research pedagogy in EFL contexts and highlight the value of collaboratively informed material development to enhance students’ research competence.